The SR protein RSP-2 influences expression of the truncated insulin receptor DAF-2B in Caenorhabditis elegans - Bryan A Martinez; Matthew S Gill (G3: Genes, Genomes, Genetics, 2023)

(untitled)
AbstractThe alternatively spliced daf-2bCaenorhabditis elegansdaf-2brsprsp-2daf-2bdaf-2brsp-2rsp-2daf-2brsp-2daf-rsp-2daf-2b.C. elegans